Archives Effectiveness in Improving Administrative Services - Rusnaedi (Cendekiawan Indonesia Timur, 2022)
Archiving is very important in an organization, office, or government; archives provide information and a vehicle for documentation. Every employee in an organization, office, or government is required to work effectively and efficiently in supporting organizational goals; so that employees can work effectively, the quality and quantity must be to the organization's needs. This study uses a quantitative research approach. Furthermore, the data that is explored includes primary and secondary data. Data collection techniques through observation, interviews, and documentation. Data has been collected through questionnaires and processed manually with a card system. Based on the results of this processing, the data is tabulated into a frequency table to determine the level of the analyzed variables. The results showed that the effectiveness of archives in improving administrative services in Bulu-Bulu Village, Tonra District, Bone Regency, namely the procedure for creating archives in managing letters was good but had not used a letter sorting tool to sort letters, both incoming and outgoing letters, which made it easier for management to be faster and easier effective. In addition, the Bulu-Bulu Village Office still uses manual archive management but does not use electronics.